Train to gain - The benefits of employee-financed training in Germany - Pfeifer, Harald [Verfasser] (My University, 2008)
"Individual returns on continuing vocational training have been in the focus of many empirical and theoretical papers. Most of the works do not explicitly discuss returns to training that is financed fully or partly by the employee. This seems surprising since several publicly funded programs to increase training participation aim at a stronger employee involvement in the financing of continuing vocational training. This paper analyses the participation in and the determinants and effects of employee-financed training using German panel data. The question is addressed, which employees invest and which benefit from training. Results show that employee-investment in training yields only moderate wage returns and has no significant impact on the further career development, especially when compared to the effects of enterprise-financed training. On the other hand, employees financing their own training gain in terms of unemployment risk reduction and the improvement in the matching of individual skills and job requirements." (Autorenreferat, BIBB-Doku)
Keywords: S 1.5.2 Berufliche Weiterbildung; S 4.3.6 Human Capital; Berufliche Weiterbildung; Bildungsertrag; Humankapital; Bildungsökonomie; Bundesrepublik Deutschland